EVALUASI IMPLEMENTASI SUPERVISI PEMBELAJARAN PADA SEKOLAH DASAR NEGERI 002, 005, DAN 012 SAMARINDA SEBERANG - Renny Puspita Sari (DAS Institute, 2022)
The aim of this research was to determine the planning, implementation, follow-up, and the result of evaluation of educational supervision implementation conducted by the Principals of State Elementary School 005, 008, and 012 Samarinda Seberang. The type of research that was used was research evaluation with gap model. This research used qualitative approach that was aimed to understand the social phenomena from the participants’ point of view. The data collection instruments used were non-test instruments which included interviews, observation, and document analysis. The collected data were analysed by using Discrepancy Evaluation Model (DEM) technique. The data analysis consists of three lines of activities that occurred simultaneously, namely: (1) data reduction; (2) data presentation; and (3) drawing conclusions. The results show that the educational supervision program made by the Principals had run well.